KAJIAN FUNGSI LEGISLASI DEWAN PERWAKILAN RAKYAT DI MASA PANDEMI - Rizki, Muhammad Riyan (Jurnal Hukum Magnum Opus, 2022)
Abstract One of the functions of the House of Representatives is to form laws and regulations, which is called the legislative function. Regarding the legislative function of the House of Representatives, it is important to see how the performance of the legislation carried out by the House of Representatives during the Covid-19 Pandemic, where there are several problems which include the legislative function of the House of Representatives during a pandemic, namely related to the quantity of legislative products produced, the process the formation of legislation products, up to and also related to the compliance of the House of Representatives in following the procedures for the formation of laws and regulations. In writing this research article, the form of research used is normative juridical, namely by analyzing secondary legal sources such as legislation or books through literature study to see the function of legislation by the House of Representatives during a pandemic. namely by using a descriptive approach to explain the quantity of legislative products made by the House of Representatives and also related to the procedural manufacture of statutory products that have been regulated in Law Number 15 of 2019 concerning Legislation. Keywords: house of representative; legislation; pandemic Abstrak Salah satu fungsi Dewan Perwakilan Rakyat adalah membentuk peraturan perundang-undangan yang disebut dengan fungsi legislasi. Terkait fungsi legislasi Dewan Perwakilan Rakyat, penting untuk melihat bagaimana kinerja legislasi yang dilakukan oleh Dewan Perwakilan Rakyat di kala Pandemi Covid-19, dimana terdapat beberapa permasalahan yang meliputi fungsi legislasi Dewan Perwakilan Rakyat di kala pandemi, yaitu terkait kuantitas produk legislasi yang dihasilkan, proses pembentukan produk legislasi, hingga dan juga terkait kepatuhan Dewan Perwakilan Rakyat dalam mengikuti prosedur pembentukan peraturan perundang-undangan. Dalam penulisan artikel penelitian ini ini, bentuk penelitian yang digunakan adalah yuridis normatif yaitu dengan menganalisis sumber hukum sekunder seperti peraturan perundang-undangan atau buku melalui studi kepustakaan untuk melihat fungsi legislasi oleh Dewan Perwakilan Rakyat di masa pandemi.Selain itu dilihat dari sifat penelitian ini, yaitu dengan menggunakan pendekatan deskriptif untuk menjelaskan tentang kuantitas produk legislasi yang dibuat oleh Dewan Perwakilan Rakyat dan juga terkait prosedural pembuatan produk perundang-undangan yang telah diatur dalam Undang-Undang Nomor 15 Tahun 2019 tentang Peraturan Perundang-Undangan Kata kunci: dewan perwakilan rakyat; legislasi; pandemi